Method for improving leaching rate of acid leaching vanadium extraction of vanadium-titanium-iron concentrate

By adding hematite powder, lime and calcium sulfate to vanadium iloxane concentrate, and using two-stage preheating and roasting processes, the problems of high vanadium loss and low leaching rate during vanadium oxidation and vanadium extraction are solved, and efficient and economical vanadium extraction effect is achieved.

CN119736488AActive Publication Date: 2025-04-01CENT SOUTH UNIV +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411979981.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-01
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The prior art has problems such as high vanadium loss and low vanadium leaching rate in vanadium iloxidation and vanadium extraction process in vanadium iloxidation and vanadium leaching rate, and the process cost is high.

Method used

By adding hematite powder, slurry lime and calcium sulfate to vanadium iloxane concentrate, and using two-stage preheating and roasting process, the porosity and oxidation conditions of the pellets are optimized, and the degree of oxidation of vanadium oxides is improved.

Benefits of technology

The vanadium leaching rate of vanadium iloxane concentrate acid leaching is significantly improved, the iron leaching rate is reduced, the process energy consumption is reduced, and the comprehensive utilization efficiency of resources is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736488A_ABST
    Figure CN119736488A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of metallurgy, and particularly relates to a method for improving the leaching rate of acid leaching vanadium extraction of vanadium-titanium-iron concentrate. The method comprises the steps that vanadium-titanium-iron concentrate and hematite powder are subjected to high-pressure roller grinding pretreatment and then mixed with slaked lime and calcium sulfate, pelletizing is conducted after wet grinding pretreatment, vanadium-titanium-iron concentrate alkaline pellets are prepared after preheating roasting, the pellets are leached through dilute acid, vanadium-containing mother liquor is obtained, and vanadium is recycled; the addition amount of the hematite powder is 4.5-11% of the mass of the vanadium-titanium-iron concentrate, the addition amount of the slaked lime is 1-5% of the mass of the vanadium-titanium-iron concentrate, and the addition amount of the calcium sulfate is 0.5-3.0% of the mass of the vanadium-titanium-iron concentrate. According to the method, bentonite is prevented from being used in the pellet preparation process, vanadium oxide oxidation is strengthened in the calcification roasting process, the porosity of the pellets is optimized, and then the vanadium leaching rate of the vanadium-titanium-iron concentrate roasted pellets is remarkably increased. The process is simple and controllable, the leaching rate of vanadium is high, the leaching rate of other impurities is low, and industrial application is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metallurgy, and in particular relates to a method for improving the leaching rate of vanadium from vanadium-titanium iron concentrate by acid leaching. Background Art

[0002] Vanadium is widely used in the steel, aviation, chemical, new energy and other industries, of which 85% is used in the steel industry. However, with the development of energy storage batteries, the demand for vanadium is also increasing. Vanadium products currently mainly include vanadium oxides such as V2O5 and V2O3, and alloy products such as ferrovanadium, vanadium aluminum, and vanadium nitride. Vanadium-titanium magnetite is an important vanadium-containing mineral resource. According to statistics, 88% of the world's annual vanadium production comes from vanadium-titanium magnetite. my country's vanadium-titanium magnetite reserves rank third in the world, of which Panzhihua, Sichuan has a reserve of 10 billion tons and Chengde, Hebei has a reserve of 8 billion tons. The vanadium content of vanadium-titanium magnetite (in terms of V2O5) is 0.2% to 2.5%.

[0003] At present, there are two main methods for extracting vanadium from vanadium-titanium iron concentrate. The first is to make vanadium-titanium iron concentrate into oxidized pellets, and then make iron and blow vanadium in converter to obtain vanadium slag, and then extract vanadium from the vanadium slag. The mainstream process of vanadium-titanium iron concentrate oxidation-blast furnace reduction-converter blowing vanadium slag-vanadium slag sodium roasting-water leaching-ammonium salt precipitation of vanadium is formed. On this basis, the process of vanadium-titanium iron concentrate oxidation-blast furnace reduction-hot iron blowing vanadium slag-vanadium slag calcification roasting-acid leaching-hydrolysis vanadium precipitation has been developed. The main problem of this process is that a large amount of vanadium is lost in the process of vanadium-titanium iron concentrate oxidation pellets through blast furnace reduction-converter blowing vanadium. According to statistics, about 40% of vanadium is lost in the process of blast furnace reduction-converter blowing vanadium. At present, the overall recovery rate of vanadium in vanadium-titanium magnetite in Panxi area is less than 50%.

[0004] For this purpose, a direct vanadium extraction process from vanadium-titanium iron concentrate has been developed, namely, the sodium roasting-water leaching-ammonium salt vanadium precipitation process of vanadium-titanium iron concentrate. A certain amount of sodium salt is added to the vanadium-titanium iron concentrate, and the vanadium is converted into water-soluble sodium vanadate through sodium roasting. After vanadium extraction through water leaching, the vanadium recovery rate can reach 80%. However, the main problem is that in order to improve the vanadium conversion rate during the sodium roasting process, sodium salt needs to be added excessively, which produces toxic gases during the roasting process, and a large amount of sodium salt still remains in the iron concentrate after water leaching, making it difficult to recover iron and titanium resources. In order to solve the problem of removing sodium from the iron concentrate after sodium roasting of vanadium-titanium iron concentrate, a vanadium-titanium iron concentrate calcium roasting-acid leaching vanadium extraction-ammonium salt vanadium precipitation process has been developed. Calcium salt is used instead of sodium salt to reduce the generation of waste gas during the roasting process, which is also conducive to the subsequent recycling of iron and titanium resources. However, the main problem of this process is that the reactivity of calcium salt is weaker than that of sodium salt, resulting in low vanadium conversion rate in the calcination roasting process. At the same time, the calcium sulfate formed in the acid leaching process hinders the leaching kinetics of vanadium, resulting in the vanadium leaching rate of the calcination roasting-acid leaching process being lower than that of the sodium roasting-water leaching process.

[0005] Patent application CN 118497484 A discloses "a comprehensive extraction and separation method for vanadium, titanium and iron in vanadium-titanium magnetite". This method obtains vanadium-containing leachate and leaching residue by calcination roasting-acid leaching. The vanadium-containing leachate is adjusted by pH to obtain iron hydroxide precipitate and ammonium metavanadate product. The application uses calcium oxide or calcium carbonate as the calcifying agent, and directly roasts the powder after mixing. Under the conditions of hot acid stirring leaching, the vanadium leaching rate in vanadium-titanium iron concentrate can reach 92.35%. Although the use of powder roasting can strengthen the solid phase reaction between vanadium-titanium iron concentrate and calcifying agent, and improve the vanadium oxidation and conversion rate, the rotary kiln powder roasting process is prone to ring formation. At the same time, the acid leaching process uses hot acid, stirring, high liquid-solid ratio and other methods to strengthen leaching, but the high liquid-solid ratio leads to too low vanadium concentration in the leachate, and the leaching mother liquor needs to be enriched before vanadium precipitation treatment can be carried out, resulting in high cost of vanadium extraction process of vanadium-titanium iron concentrate.

[0006] Patent application CN 107090551 A discloses "a method for direct vanadium extraction from vanadium-titanium magnetite", which uses vanadium-titanium magnetite to add carbon-based additives and calcifying agents for calcification roasting, and obtains a vanadium-containing leaching solution after ammoniation. The application adopts the method of adding carbon-based additives to destroy the spinel structure of vanadium-titanium iron concentrate. At the same time, the carbon-based additives decompose in an oxidizing atmosphere to produce CO2, which can increase the permeability of the material and has an anti-adhesion effect. Although the addition of carbon-based additives can improve the permeability of vanadium-titanium iron concentrate pellets and increase the vanadium conversion rate, the formation of CO2 will reduce the oxygen partial pressure inside the pellets, thereby destroying the oxidizing atmosphere, resulting in a decrease in the vanadium oxidation rate in the vanadium-titanium iron concentrate, and thus affecting the subsequent vanadium extraction rate.

[0007] Patent CN201210137458.2 discloses a "method for recovering vanadium from vanadium-titanium magnetite". Vanadium-titanium magnetite, calcium additives and binders are mixed to form balls, dried, and then oxidized and roasted to obtain roasted clinker. After carbonation leaching, vanadium-containing leachate and vanadium-extracted pellets are obtained. The oxidative roasting process uses a strong oxidizing atmosphere such as oxygen, oxygen-enriched air, and ozone to strengthen the oxidation of vanadium in vanadium-titanium iron concentrate to increase the subsequent vanadium leaching rate. Although this method can strengthen the atmosphere of the oxidation process of vanadium-titanium iron concentrate pellets, it is still difficult for the oxidizing gas to reach the inside of the pellets, resulting in a low vanadium oxidation rate and a low vanadium leaching rate.

[0008] In summary, the current methods for strengthening vanadium oxidation during calcination roasting of vanadium-titanium iron concentrate are: 1) using powder roasting; 2) increasing the porosity of the pellets to strengthen the oxidative atmosphere inside the pellets; 3) using a strong oxidizing atmosphere during the calcination roasting process to promote vanadium oxidation conversion. However, it is difficult for the above methods to achieve full oxidation of vanadium oxides in vanadium-titanium iron concentrate economically and efficiently, and to improve the vanadium leaching rate in the calcination roasting-acid leaching process. In order to solve the above problems, the present invention proposes a method for improving the vanadium leaching rate of acid leaching of vanadium-titanium iron concentrate. Summary of the invention

[0009] The present invention provides a method for improving the vanadium leaching rate of vanadium-titanium iron concentrate acid leaching; the present invention avoids the use of bentonite in the pellet preparation process, and at the same time strengthens the oxidation of vanadium oxides in the calcination roasting process, optimizes the porosity of the pellets, and thus significantly improves the vanadium leaching rate of the roasted pellets of vanadium-titanium iron concentrate. To achieve the above purpose, this patent includes the following steps: A method for improving the leaching rate of vanadium by acid leaching of vanadium-titanium iron concentrate, the method comprising: pre-treating the vanadium-titanium iron concentrate and hematite powder by high-pressure roller mill, mixing with slaked lime and calcium sulfate, and then pre-treating with wet grinding to form balls, preparing alkaline balls of the vanadium-titanium iron concentrate after preheating and roasting, and leaching the balls with dilute acid to obtain a vanadium-containing mother liquor to recover vanadium.

[0010] The steps include: (1) After the vanadium-titanium iron concentrate and hematite powder are pre-treated by high-pressure roller mill, they are fully mixed with slaked lime and calcium sulfate in a certain proportion and then pre-grinded; the amount of hematite powder added is 4.5-11% of the mass of the vanadium-titanium iron concentrate. The amount of slaked lime added is 1-5% of the mass of the vanadium-titanium-iron concentrate, and the amount of calcium sulfate added is 0.5-3.0% of the mass of the vanadium-titanium-iron concentrate; (2) pelletizing the mixed materials, drying, preheating and roasting the qualified green balls to obtain vanadium-titanium magnetite alkaline pellets; (3) The roasted pellets are subjected to acid leaching to extract vanadium, and vanadium can be recovered from the vanadium extraction mother liquor.

[0011] Preferably, in step (1), by mass percentage, the vanadium-titanium magnetite concentrate contains 50-60% TFe, 8-15% TiO2, and 0.5-1.50% V2O5; and the hematite contains 60-65% TFe.

[0012] Preferably, the particle size of the vanadium-titanium iron concentrate and hematite powder in step (1) is not less than 80wt% at -200 mesh.

[0013] Preferably, the amount of hematite powder added is 5-10% of the mass of the vanadium-titanium iron concentrate, the amount of slaked lime added is 2-5% of the mass of the vanadium-titanium iron concentrate, and the amount of calcium sulfate added is 1.5-3.0% of the mass of the vanadium-titanium iron concentrate.

[0014] Preferably, the calcifying agent in step (1) is dry slaked lime, which is slaked lime produced from CaO by dry digestion process, wherein CaO≥70%, particle size +100 mm≤5%, bulk density≤0.5 g / ml; CaO≥30% in calcium sulfate, particle size -200 mesh≥90%.

[0015] Preferably, the pelletizing in step (2) is to add 0.5-1.0% water to the mixed material in a disc pelletizing machine, and the raw balls are screened out with 16 mm and 9 mm roller screening machines to obtain qualified raw balls of 9-16 mm.

[0016] Preferably, the drying in step (2) is carried out at a temperature of 200 to 400° C. and a drying time of 5 to 10 min. Preferably, the first stage preheating in step (2) has a preheating temperature of 700-900° C. and a preheating time of 5-10 min.

[0017] Preferably, the preheating temperature in step (2) is 900-1100°C, the preheating time is 8-15 min, and Fe 2+ ≤0.5%; Preferably, the calcination temperature in step (2) is 1100-1250°C, the calcination time is 10-15 min, and Fe 2+ ≤0.3%, the average compressive strength of the roasted pellets is 1500~2500N / piece; Preferably, in the acid leaching of step (3), the acid in the dilute acid solution is a mixture of one or more of sulfuric acid, nitric acid or hydrochloric acid solution, [H + ] concentration is 0.1 to 4 mol, the acid leaching dilute acid solution contains V, Fe, Al ions, and the V concentration is 3 to 6 g / l. The vanadium leaching method is heap leaching, column leaching or immersion, multi-stage leaching, preferably 4-stage leaching plus one-stage washing, the leaching temperature is room temperature, the liquid-solid ratio is 0.3 to 5.0, and the leaching time is 5 to 30 days.

[0018] The mechanism mainly involved in the present invention is as follows: The vanadium element in vanadium-titanium iron concentrate is mainly present in the spinel structure of titanomagnetite. In order to achieve the full oxidation of iron and vanadium oxides in vanadium-titanium iron concentrate, the spinel structure of titanomagnetite must be destroyed first. And the oxidation of iron and vanadium oxides depends on the oxidation temperature and oxygen concentration of the preheating roasting process. Higher oxidation temperature and oxygen concentration are conducive to the full oxidation of iron and vanadium oxides. In the roasting and consolidation process of vanadium-titanium iron concentrate pellets at 1150~1250℃, although the oxidation temperature is high, the microcrystalline bond connection of titanium hematite inside the pellets is fully developed at this stage, resulting in a decrease in the porosity of the pellets and a low oxygen concentration inside the pellets, which is not conducive to the full oxidation of iron and vanadium oxides. Therefore, the present invention adds two stages of preheating oxidation before the pellets are roasted and consolidated, and the porosity of the preheated pellets is high, and oxygen is easily diffused into the pellets. In the first preheating stage at 700-900℃, the spinel structure of titanomagnetite is destroyed, and the vanadium oxide is fully exposed and partially oxidized; in the second preheating stage at 900-1100℃, the higher oxidation temperature and sufficient oxidizing atmosphere are conducive to the rapid oxidation of V2O3 and FeO in the vanadium-titanium iron concentrate, and this oxidation process is conducive to shortening the subsequent roasting and consolidation time. After the vanadium-titanium iron concentrate pellets are fully oxidized after two preheating stages, the Fe 2+ The content of V 5+The content is significantly increased, which is beneficial to the subsequent acid leaching process to increase the vanadium leaching rate and reduce the iron leaching rate. The most critical thing is that the present invention also adds an appropriate amount of hematite powder, which can further enhance the oxidation conversion of vanadium under the action of the above-mentioned preheating oxidation mechanism, and is more conducive to the leaching of vanadium. The present invention uses an appropriate amount of slaked lime and calcium sulfate as additives with an appropriate amount of hematite powder, and qualified pellets can be obtained without bentonite, and the leaching rate of vanadium is significantly improved.

[0019] Differences from existing technologies: 1) The output of Panxi vanadium-titanium iron concentrate is 38.6 million tons / year. The vanadium industry chain in Panxi Economic Zone is to make iron first and then extract vanadium. Therefore, the extension and expansion of the vanadium industry chain are heavily dependent on the steel industry chain. At the same time, about 40% of the vanadium is not extracted in the process of blast furnace ironmaking-converter vanadium blowing to prepare vanadium slag, resulting in the waste of vanadium resources in vanadium-titanium iron concentrate. It is an inevitable trend to directly extract vanadium from vanadium-titanium iron concentrate. However, patent application CN 201710317661.3 adopts the method of grinding the roasted pellets to -200 mesh, leaching for 1~3h at 90℃, liquid-solid ratio of 30~50:1 and stirring. There are three major problems in the industrialization of this patented technology: 1) 30-50 tons of leaching solution need to be heated to 90°C and stirred for 1-3 hours for every ton of ore processed, and the energy consumption of this process is too high; 2) Since the V2O5 content in vanadium-titanium iron concentrate is only about 0.6%, the maximum V2O5 concentration in the vanadium mother liquor of this patented technology does not exceed 0.18 g / l, and the subsequent vanadium enrichment and extraction cost is high; 3) It is difficult to efficiently and comprehensively utilize the iron concentrate after vanadium extraction at -200 mesh, resulting in a waste of titanium-iron resources. This patent optimizes the thermal system of the calcification roasting process of vanadium-titanium iron concentrate, promotes the full oxidation of iron and vanadium oxides, significantly improves the vanadium leaching rate and reduces the iron leaching rate under low liquid-solid ratio and room temperature heap leaching conditions, and can effectively solve the problems of high energy consumption in the vanadium extraction process, low vanadium mother liquor concentration, and comprehensive utilization of iron-containing resources after acid leaching.

[0020] 2) The prior art uses the traditional iron ore pellet thermal system to prepare vanadium-titanium iron concentrate calcified roasted pellets. The preheating stage has a low temperature and a short time. It is only used to prepare preheated pellets with qualified strength, and does not consider the oxidation behavior of iron and vanadium oxides during the preheating process of vanadium-titanium iron concentrate pellets. Vanadium-titanium iron concentrate is a typical complex ore. Compared with ordinary iron ore, its oxidation is more difficult. It is difficult to fully oxidize the iron and vanadium oxides in the vanadium-titanium iron concentrate pellets using the traditional iron ore pellet preheating system. Therefore, the present invention adopts a two-stage preheating method in the preparation process of preheated pellets. In the first preheating stage at 700~900℃, the spinel structure of titanium magnetite is destroyed, so that the vanadium oxide is fully exposed and partially oxidized; in the second preheating stage at 900~1100℃, the preheating temperature is increased and the preheating time is extended to fully oxidize the iron and vanadium oxides. This step significantly reduces the Fe in the preheated pellets. 2+ content, and significantly increase V 5+ In the sulfuric acid leaching process, V5+ The leaching rate is significantly higher than that of V 4+ 、V 3+ ; and Fe 3+ The leaching rate is significantly lower than that of Fe 2+ Therefore, the thermal system proposed in the present invention is beneficial to improving the vanadium leaching rate, reducing the iron leaching rate and shortening the leaching time in the acid leaching process of calcified roasted pellets of vanadium-titanium iron ore concentrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a physical picture of the vanadium-titanium iron concentrate in Example 5; Figure 2 This is a physical picture of the pellet particles after vanadium immersion in Example 5. DETAILED DESCRIPTION

[0022] The present invention is further described below with reference to specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.

[0023] The typical physical properties of the vanadium-titanium iron concentrate used in the examples of the present invention and the comparative examples are shown in Table 1, the typical particle size composition of the vanadium-titanium iron concentrate is shown in Table 2, and the typical chemical composition of the vanadium-titanium iron concentrate is shown in Table 3.

[0024]

[0025]

[0026]

[0027] The slaked lime used in the embodiment of the present invention is dry slaked lime, which is slaked lime produced from CaO using a dry digestion process, wherein CaO ≥ 70%, particle size + 100 mm ≤ 5%, bulk density ≤ 0.5 g / ml; CaO ≥ 30% in calcium sulfate, particle size - 200 mesh ≥ 90%.

[0028] Example series 1 (including comparative cases) The vanadium-titanium iron concentrate and 10% hematite powder were pre-treated by high-pressure roller mill, and then mixed with 1.5% slaked lime and 1% calcium sulfate for 3 minutes, and pelletized in a disc pelletizer. The diameter of the balls was 12±2 mm, and the moisture content of the raw balls was 7.89%. After drying at 400°C for 15 minutes, they were roasted according to the conditions in Table 1-1. The Fe content in the pellets prepared by the roasting system of the present invention is 2+ The content is 0.26%; while the Fe content in the pellets prepared by the conventional roasting system is 2+The content is 3.48%. The two-stage preheating step significantly improves the oxidation degree of iron oxides and vanadium oxides in the pellets. At the same time, the roasting temperature of the present invention is reduced to 1170°C, and the porosity of the prepared roasted pellets is 21.49%, which is significantly higher than the porosity of 14.45% of the roasted pellets prepared under the conventional roasting system. The developed pore distribution and high porosity of the calcified roasted pellets are conducive to improving the vanadium leaching kinetics of the acid leaching process, increasing the vanadium leaching rate and shortening the leaching time. The three types of calcified roasted pellets were subjected to vanadium extraction experiments under the same acid leaching conditions, and the vanadium leaching rates were 62.69% (conventional-1); 53.21% (conventional-2); 85.78% (the present invention). The acid leaching results of the calcified roasted pellets of vanadium-titanium iron concentrate show that by optimizing the thermal system, the oxidation degree of iron and vanadium oxides and the porosity of the calcified roasted pellets are improved, thereby significantly improving the vanadium leaching rate of the acid leaching process.

[0029]

[0030] Example 2 The vanadium-titanium iron concentrate and 5% hematite powder were pre-treated by high-pressure roller mill, and then mixed with 1.0% slaked lime and 3% calcium sulfate for 3 minutes, and pelletized in a disc pelletizer. The diameter of the balls was 12±2 mm and the water content was 7.35%. After drying at 400°C for 15 minutes, the chain grate-rotary kiln process was used for preheating and roasting according to the conditions of the present invention in Table 1-1. The Fe 2+ 500g of pellets were placed in 8 1000ml measuring cylinders and leached vanadium by immersion at room temperature. The liquid-to-solid ratio was 2 and the acid concentration of the leaching solution [H + ] were 1.2M, 1.5M, 1.8M, 2.0M, 2.5M, and 3.0M, respectively, and the acid was added every day according to the consumption of the leaching solution. After 27 days of immersion and 1 day of washing, the vanadium leaching rates were 77.19%, 78.64%, 79.31%, 79.56%, 83.22% and 85.45%, respectively.

[0031] Example 3 The vanadium-titanium iron concentrate and 5% hematite powder were pre-treated by high-pressure roller mill, and then mixed with 5% slaked lime and 0.5% calcium sulfate for 3 minutes, and pelletized in a disc pelletizer. The ball diameter was 12±2 mm and the water content was 7.99%. After drying at 400°C for 15 minutes, the grate-rotary kiln process was used for roasting according to the conditions of the present invention in Table 1-1. Fe in the pellets 2+ 500g of pellets were placed in four 1000ml measuring cylinders and leached at room temperature. The liquid-to-solid ratio was 2 and the acid concentration of the leaching solution [H +] were 1.2M, 1.6M, 2.0M, 2.5M, and 3.0M, and were replenished every day according to the consumption of leaching solution acid. After 27 days of immersion and 1 day of washing, the vanadium leaching rates were 75.79%, 77.50%, 80.89%, 82.62%, and 86.31%, respectively.

[0032] Example 4 The vanadium-titanium iron concentrate and 10% hematite powder were pre-treated by high-pressure roller mill, and then mixed with 2.0% dry slaked lime and 1.5% calcium sulfate for 3 minutes, and pelletized in a disc pelletizer. The ball diameter was 12±2 mm and the water content was 7.96%. After drying at 400°C for 15 minutes, the grate-rotary kiln process was used for roasting according to the conditions of the present invention in Table 1-1. Fe in the pellets 2+ 500g of pellets were placed in four 1000ml measuring cylinders and leached at room temperature. The liquid-to-solid ratio was 2 and the acid concentration of the leaching solution was [H + ] were 1.2M, 1.6M, 2.0M, 2.5M, and 3.0M, and were replenished every day according to the consumption of leaching solution acid. After 27 days of immersion and 1 day of washing, the vanadium leaching rates were 76.05%, 80.53%, 80.64%, 83.23%, and 86.88%, respectively.

[0033] Example 5 The vanadium-titanium iron concentrate and 5% hematite powder were pre-treated by high-pressure roller mill, and then mixed with 3.0% dry slaked lime and 2% calcium sulfate for 3 minutes, and pelletized in a disc pelletizer. The ball diameter was 12±2 mm and the water content was 8.00%. After drying at 400℃ for 15 minutes, the laboratory muffle furnace was used for heating and roasting. The roasting treatment was carried out under the following conditions: first stage preheating: 900℃, 10 minutes; second stage preheating: 1050℃, 20 minutes; roasting: 1150℃, 15 minutes. Fe in the pellets 2+ The content is 0.39%.

[0034] 500g of pellets were placed in a 1000ml measuring cylinder and leached at room temperature. The liquid-to-solid ratio was 2 and the acid concentration of the leaching solution [H + ] were 3.0M respectively, and the acid was added every day according to the consumption of leaching solution. After 27 days of immersion and 1 day of washing, the leaching rates of vanadium and iron were 87.27% and 1.77% respectively.

[0035] Comparative Example 1 The other systems were the same as those in Example 4, except that no hematite powder was added. 500 g of pellets were placed in a 1000 ml measuring cylinder and leached at room temperature. The liquid-to-solid ratio was 2, and the acid concentration of the leaching solution [H +] were 3.0 M, and the acid was added every day according to the consumption of leaching solution. After 27 days of immersion and 1 day of washing, the leaching rates of vanadium and iron were 78.38% respectively.

[0036] Comparative Example 2 The other conditions were the same as those in Example 4, except that no slaked lime was added, 500 g of pellets were placed in a 1000 ml measuring cylinder, and vanadium was leached at room temperature by immersion, the liquid-to-solid ratio was 2, and the acid concentration of the leaching solution [H + ] were 3.0M respectively, and the acid was added every day according to the consumption of leaching solution. After 27 days of immersion and 1 day of washing, the leaching rates of vanadium and iron were 72.38% respectively.

[0037] Comparative Example 3 The other conditions were the same as those in Example 4, except that calcium sulfate was not added, 500 g of pellets were placed in a 1000 ml measuring cylinder and leached at room temperature, the liquid-to-solid ratio was 2, and the acid concentration of the leaching solution [H + ] were 3.0 M, and the acid was added every day according to the consumption of leaching solution. After 27 days of immersion and 1 day of washing, the leaching rates of vanadium and iron were 75.38% respectively.

Claims

1. A method for improving the leaching rate of vanadium from vanadium-titanium iron concentrate by acid leaching, characterized in that: The vanadium-titanium iron concentrate and hematite powder are pretreated by high-pressure roller mill, mixed with slaked lime and calcium sulfate, and then pretreated by wet grinding to form balls. After preheating and roasting, alkaline pellets of the vanadium-titanium iron concentrate are prepared. The pellets are leached with dilute acid to obtain vanadium-containing mother liquor to recover vanadium; the amount of hematite powder added is 4.5-11% of the mass of the vanadium-titanium iron concentrate, the amount of slaked lime added is 1-5% of the mass of the vanadium-titanium iron concentrate, and the amount of calcium sulfate added is 0.5-3.0% of the mass of the vanadium-titanium iron concentrate.

2. The method for improving the leaching rate of vanadium from vanadium-titanium iron ore concentrate according to claim 1, characterized in that: The steps include: (1) Pre-treatment of vanadium-titanium iron concentrate and hematite powder by high-pressure roller mill, and then fully mix with slaked lime and calcium sulfate in a certain proportion and then perform pre-treatment by wet grinding; (2) pelletizing the mixed materials, drying, preheating and roasting the qualified green balls to obtain vanadium-titanium magnetite alkaline pellets; (3) The roasted pellets are subjected to acid leaching to extract vanadium, and vanadium can be recovered from the vanadium extraction mother liquor; In step (1), by mass percentage, the vanadium-titanium magnetite concentrate contains 50-60% TFe, 8-15% TiO2, and 0.5-1.50% V2O5; the hematite contains 60-65% TFe; The particle size of the vanadium-titanium iron concentrate and hematite powder in step (1) is not less than 80% at -200 mesh.

3. The method for improving the leaching rate of vanadium by acid leaching of vanadium-titanium iron ore according to claim 1, characterized in that: The amount of hematite powder added is 5-10% of the mass of the vanadium-titanium iron concentrate. The amount of slaked lime added is 2-5% of the mass of the vanadium-titanium iron concentrate, and the amount of calcium sulfate added is 1.5-3.0% of the mass of the vanadium-titanium iron concentrate.

4. The method for improving the leaching rate of vanadium by acid leaching of vanadium-titanium iron ore according to claim 1, characterized in that: The calcifying agent in step (1) is dry slaked lime, which is slaked lime produced from CaO by dry digestion process, wherein CaO≥70%, particle size +100 mm≤5%, bulk density≤0.5 g / ml; CaO≥30% in calcium sulfate, particle size -200 mesh≥90%.

5. The method for improving the leaching rate of vanadium by acid leaching of vanadium-titanium iron ore according to claim 1, characterized in that: The pelletizing in step (2) is to add 0.5-1.0% water to the mixed material in a disc pelletizing machine, and the raw balls are screened out with 16 mm and 9 mm roller screening machines to obtain qualified raw balls of 9-16 mm.

6. The method for improving the leaching rate of vanadium from vanadium-titanium iron concentrate according to claim 1, characterized in that: The drying in step (2) is carried out at a temperature of 200 to 400° C. and for a time of 5 to 10 min.

7. The method for improving the leaching rate of vanadium from vanadium-titanium iron ore concentrate according to claim 1, characterized in that: The first stage preheating described in step (2) has a preheating temperature of 700-900° C. and a preheating time of 5-10 min.

8. The method for improving the leaching rate of vanadium by acid leaching of vanadium-titanium iron ore according to claim 1, characterized in that: The preheating temperature in step (2) is 900-1100°C, the preheating time is 8-15 min, and Fe 2+ ≤0.5%.

9. The method for improving the leaching rate of vanadium by acid leaching of vanadium-titanium iron ore according to claim 1, characterized in that: The calcination temperature in step (2) is 1100-1250°C, the calcination time is 10-15 min, and Fe 2+ ≤0.3%, the average compressive strength of the calcined pellets is 1500~2500N / piece.

10. The method for improving the leaching rate of vanadium by acid leaching of vanadium-titanium iron ore according to claim 1, characterized in that: In the acid leaching of step (3), the acid in the dilute acid solution is a mixture of one or more of sulfuric acid, nitric acid or hydrochloric acid solution, [H + ] concentration is 0.1 to 4 mol, the dilute acid solution contains V, Fe, Al ions, and the V concentration is 3~6g / l. The vanadium leaching method is heap leaching, column leaching or soaking, multi-stage leaching, preferably 4-stage leaching plus one-stage washing, the leaching temperature is room temperature, the liquid-solid ratio is 0.3~5.0, and the leaching time is 5 to 30 days.

Citation Information

Patent Citations

  • Methods for recovering vanadium from vanadium-titanium magnetite

    CN102703688B

  • Direct vanadium extracting method for vanadium-titanium magnetite

    CN107090551A

  • Method and system for controlling storage terminal to store articles

    CN107195126A

  • Method for directly extracting vanadium from vanadium titan magnetite concentrate

    CN101358301A

  • Method for extracting vanadium by sodium salt roasting from vanadium-bearing iron concentrate

    CN109797297A